The Return of light : a Christmas tale - Calhoun, Dia (Marshall Cavendish, 2007)
When the Christmas Deer chooses him for the Christmas harvest, Treewing, a five-year-old tree, is surprised since it is a year early, but is told he has been picked for a special destiny.